Langt mere eventyrligt end historisk - Grell, Helge (Grundtvig-Studier, 1993)
»Langt mere eventyrligt end historisk« Om Grundtvigs forhold til England By Helge Grell In a letter to Queen Caroline Amalie, written towards the end of his Englandjoumey in 1843, Grundtvig describes his attitude to England as ’more fantastic than historical’. This expression is only comprehensible when viewed within the tension created by his expectation of finding a receptive forum for his ideas among the English and his subsequent disappointment. The English, whom Grundtvig met, proved un-receptive, not only to his view of universal history, including the central role he allocated to the English people, but also to his ecclesiastical position. The ’fantastic’ i Grundtvig’s attitude to the English is in evidence in his continued insistence on the central importance of England for his view on universal history and in the high hopes he still held for the realisation of his ecclesiastical ideas in England, despite his disappointment and his critical attitude to contemporary English life. Furthermore, Grundtvig’s attitude to England is even more ’fantastic’ when we realize that the contradiction between his expectations of the English and England and his negative experience becomes a deciding factor in his thoughts about the necessary interaction between the spiritual and the material world.